Community Involvement for Sustainable World Heritage Sites: The Melaka Case - Ong Puay Liu (Kajian Malaysia, 2017)
Melaka and Georgetown, Penang, received UNESCO recognition as a World Heritage Site (WHS) in 2008. "Historic Cities of the Straits of Malacca", both Melaka and Georgetown have heritage of outstanding universal value (OUV), which means cultural and/or natural significance so exceptional as to transcend national boundaries and be of common importance for present and future generations. Sustainable protection of this heritage is thus of highest importance to the international community. In UNESCO-initiated conventions such as the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage 2003 and UNESCO World Heritage Centre's Operational Guidelines for the Implementation of the World Heritage Convention 2015, participation of communities and individuals that create, maintain and transmit such heritage is given much emphasis. To what extent is the concept of a community-based heritage protection and conservation adopted by authorities in WHSs in their efforts to safeguard the heritage of OUV and sustain the status of their respective sites? This article argues that for sustainable continuity as a WHS, the local communities of WHSs should be regarded as the subject of development, and not as object of development, where they should be one of the principal actors, and actively involved in decisionmaking that will impact their living conditions and life. Based on Melaka as a case study, this article discusses the participation of the local communities in the planning and management of heritage protection and conservation of Melaka as a WHS. A series of consultations and focus group discussions were conducted with the various communities in 2013–2014. The research findings indicate that community participation in the planning and management process is minimal and that the local community is largely excluded from this process.